PENGARUH LATIHAN PLYOMETRIC TERHADAP TINGGI LOMPATAN VERTIKAL PEMAIN BOLA VOLI - Moh. Rifki Hidayat; Linda Andari; Anggi; Asep Sahrul Gunawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Vertical jump height is a very important physical component for volleyball players. Good jumping ability is highly required to support an athlete's success when performing main techniques, such as smashes, blocks, and jump serves. Therefore, this study aims to analyze the effect of plyometric training on the Vertical jump height of volleyball players through a literature review. This study uses a library research method with a descriptive qualitative approach. During data collection, the researcher searched various scientific articles from national and international journals. The literature search was conducted through accredited databases like Google Scholar, PubMed, and Scopus, which were then analyzed using content analysis. Based on the review of 12 main articles, it is evident that regular plyometric training can consistently improve the athletes' Vertical jump height. The most frequently applied training forms include depth jumps, box jumps, hurdle jumps, and plyometric jump training (PJT). The training duration considered most effective usually runs between 6 and 12 weeks. This improvement occurs due to neuromuscular system adaptations and the optimization of the stretch-shortening cycle, which strongly boosts the explosive power of the lower leg muscles. In conclusion, plyometric training is a proven effective method to enhance the Vertical jumping ability of volleyball athletes. The results of this literature synthesis are expected to contribute insights and serve as a foundation for coaches in designing more optimal volleyball training programs.